Adoption of biogas technology by cassava processors: Implication for environmental sustainability - Mukaila, Ridwan; Umaru, Ibrahim Isaac; Otekunrin, Olutosin Ademola; Omeje, Emmanuel Ejiofor; Awoyelu, Festus EluwandeDurojaye; Onah, Ogochukwu Gabriela; Okorie, Oguejiofor Joseph; Onyia, Chukwuemeka Chiebonam; Ezinwa, Goodness Somukenechukwu (World development sustainability, 2024)
•The cassava processors' current waste management practices resulted in an unhealthy environment.•Awareness of biogas technology for cassava waste management was very low among the processors.•However, 74.17% were willing to adopt biogas technology to manage waste after the creation of awareness.•The drivers for their adoption intention were awareness of biogas technology, age, experience, extension services, credit, and association. Improved and environmentally friendly agricultural waste management technology is needed to improve the environment and avoid some health issues as a result of poor waste management. Yet, its adoption is low and there is little documented work on the subject matter, especially in Nigeria. Therefore, this study assessed cassava processors’ willingness to adopt improved cassava waste management technology in Nigeria. Descriptive statistics and logistic regression were used to analyze data collected from 240 cassava processors using a structured questionnaire. The current cassava waste management practices among the processors were disposing of the solid waste through open dumping around the processing site, letting liquid waste run off and dry on the ground, channelling liquid waste to the drainage system, burning waste and disposing of waste on the farm. These methods caused insects and pests to breed and bad odor in the area, which resulted in an unhealthy environment and affected people's health. Awareness of biogas technology for cassava waste management was very low (21.25%) among the processors and only 10.83% were aware of its benefits. However, 74.17% were willing to adopt biogas technology to manage waste after the creation of awareness about biogas technology. The significant factors responsible for their intention to adopt improved technology were awareness of biogas technology, awareness of the benefits of biogas technology, age, experience, extension services, access to credit, and membership in an association. This study advocates the creation of awareness about modern improved waste management by institutions, and agricultural extension to have a healthy environment.